1974
DOI: 10.1136/bmj.1.5907.533
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Women Taking Oral Contraceptives

Abstract: SummaryA controlled prospective survey of women taking oestrogen-progestogen oral contraceptives showed increases in mean systolic and diastolic blood pressure of 14-2 mm Hg and 8-5 mm Hg respectively after four years. The largest increases in individual cases were 36 mm Hg systolic and 20 mm Hg diastolic. Blood pressure returned to pretreatment levels within three months after oral contraceptives had been stopped. These changes in blood pressure were unrelated to the progestogenic potencies of the preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(44 citation statements)
references
References 8 publications
1
41
1
1
Order By: Relevance
“…In another study, blood pressure fell in hypertensive women when their 50 g oestrogen pill was changed to 30 g oestrogen. 58 Contrasting findings were reported in a study, 70 in which 15 women on 30 g oestrogen OCs registered higher blood pressures than 28 women on 50 g OCs-findings attributed by the authors to the different progestogenic components. Low-dose OCs were deemed so safe following a study of women of mean age 26.3 years after 6 and 12 months of use, that the authors considered they could be safely sold over the counter.…”
Section: Target Organ Effectscontrasting
confidence: 37%
See 2 more Smart Citations
“…In another study, blood pressure fell in hypertensive women when their 50 g oestrogen pill was changed to 30 g oestrogen. 58 Contrasting findings were reported in a study, 70 in which 15 women on 30 g oestrogen OCs registered higher blood pressures than 28 women on 50 g OCs-findings attributed by the authors to the different progestogenic components. Low-dose OCs were deemed so safe following a study of women of mean age 26.3 years after 6 and 12 months of use, that the authors considered they could be safely sold over the counter.…”
Section: Target Organ Effectscontrasting
confidence: 37%
“…54 Following Woods' initial report 55 in 1967 of elevated blood pressure in hypertensive women on OCs, several investigators documented the considerable lowering of blood pressure among hypertensive women upon stopping OCs. [56][57][58][59][60] Laragh and Sealey 56 reported elevations in renin substrate concentration and aldosterone excretion, as well as abnormalities in renin activity and renin reactivity in women on OC therapy. Weinberger 57 also pointed out a rise in plasma renin substrate concentration in women on OC therapy.…”
Section: Target Organ Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Controlled prospective studies have consistently demonstrated a return of BP to pretreatment levels within 3 months of discontinuing COCs. 16,19 In the Health Survey for England, a cross-sectional survey, mean BP was significantly higher among premenopausal women who were current users of oral contraceptives (COCs and progestin-only) than among non-users. 20 The BP difference tended to increase with age.…”
Section: Oral Contraceptives and Bpmentioning
confidence: 99%
“…The association between the use of OC and BP elevation has been repeatedly demonstrated. 11,[17][18][19] In the last Joint National Committee, JNC 7 report, it is emphasized that OC raise BP and that the risk of hypertension increases with length of use. They recommend that OC users should get their pressure levels checked regularly during the period when they are taking OC and that the onset of hypertension is a reason to consider other forms of contraception.…”
Section: Discussionmentioning
confidence: 99%